Respuestas
Respuesta dada por:
1
Hola. se sabe que
![{(a + b)}^{2} - {(a - b)}^{2} = 4ab \\ {(3 \sqrt{2} )}^{2} - {(a - b)}^{2} = 4 \times 3 \\ 18 - {(a - b)}^{2} = 12 \\ 6 = {(a - b)}^{2} \\ \sqrt{6} = a - b {(a + b)}^{2} - {(a - b)}^{2} = 4ab \\ {(3 \sqrt{2} )}^{2} - {(a - b)}^{2} = 4 \times 3 \\ 18 - {(a - b)}^{2} = 12 \\ 6 = {(a - b)}^{2} \\ \sqrt{6} = a - b](https://tex.z-dn.net/?f=+%7B%28a+%2B+b%29%7D%5E%7B2%7D++-++%7B%28a+-+b%29%7D%5E%7B2%7D++%3D+4ab+%5C%5C++%7B%283+%5Csqrt%7B2%7D+%29%7D%5E%7B2%7D++-++%7B%28a+-+b%29%7D%5E%7B2%7D++%3D+4+%5Ctimes+3+%5C%5C+18+-++%7B%28a+-+b%29%7D%5E%7B2%7D++%3D+12+%5C%5C+6+%3D++%7B%28a++-+b%29%7D%5E%7B2%7D++%5C%5C++%5Csqrt%7B6%7D++%3D+a+-+b)
Adjuntos:
![](https://es-static.z-dn.net/files/dcc/44ccd88c9414dc12e92259b84dcfd2aa.jpg)
Preguntas similares
hace 6 años
hace 9 años